The Kabata Dutu (Local Wisdom) As a Means of Social Criticism of the People of Tidore - Marasabessy, Abd. Chaidir; Siagian, Amrizal; Halil, Muamar Abd. Abd. (Universitas Budi Luhur, 2023)
For centuries, for the people of Tidore (North Maluku), social control has been a tradition of their ancestors (kabata dutu). This tradition is a form of communication among the Tidore people, with the aim of controlling the functioning of a social system. This research aims to explain the kabata dutu tradition (local wisdom) as social control for the Tidore community and describe the meaning contained in the kabata dutu tradition. Primary and secondary data (interviews, literature reviews, journals, scientific articles) are the reference for this research. The data analysis knife goes through the process of searching (systematic data classification) and drawing conclusions. Research conclusions; 1) The kabata dutu tradition is the philosophy of life of the Tidore people. This tradition is part of the social expression that emerged from the lives of the Tidore people to defend matters of truth. This tradition is not just an accessory to cultural representation, but as a social control to instill a culture of shame so that all forms of action are based on social norms. Kabata dutu is a means of aspiration (social control) for the government to improve public services faced by the community. Each stage of the traditional procession reflects a social process that encourages the realization of positive character in the lives of its people; 2) Kabata dutu interprets humans as social units who are interconnected with each other, so that a sense of belonging and need is expressed in the daily lifestyle of the Tidore people. The meaning of the kabata dutu tradition is as a message (borero) from the ancestors which contains universal truth values (in all aspects of life, including morals, customs, social ties). Through kabata poetry, Tidore people exercise social control in their behavior in society in order to maintain the noble values of their ancestral mandate.